The influence of glutamatergic receptor antagonists on biochemical and ultrastructural changes in myelin membranes of rats subjected to experimental autoimmune encephalomyelitis - Dąbrowska-Bouta, Beata; Strużyńska, Lidia; Chalimoniuk, Małgorzata; Frontczak-Baniewicz, Małgorzata; Sulkowski, Grzegorz (Folia Neuropathologica, 2015)
Elevated extracellular glutamate in the synaptic cleft causes overactivation of glutamate receptors and kills neurons by an excitotoxic mechanism. Recent studies have shown that glutamate can also lead to toxic injury of white matter oligodendrocytes in myelin sheaths and consequently to axon demyelination. The present study was performed using the rodent model of multiple sclerosis known as experimental autoimmune encephalomyelitis (EAE). The aim of the study was to test the effects of the glutamatergic receptor antagonists amantadine and memantine (antagonists of NMDA receptors), LY 367384 (an antagonist of mGluR1), and MPEP (an mGluR5 antagonist) on the development of neurological symptoms in immunized animals, morphological changes in cerebral myelin, and expression of mRNA of the principal myelin proteins PLP, MBP, MOG, MAG, and CNPase. Pharmacological inhibition of NMDA receptors by amantadine and memantine was found to suppress neurological symptoms in EAE rats, whereas antagonists of the group I metabotropic glutamate receptors (mGluRs G I) did not function positively. In the symptomatic phase of the disease we observed destruction of myelin sheaths via electron microscopy and decreased levels of mRNA for all of the principal myelin proteins. The results reveal that glutamate receptor antagonists have a positive effect on the expression of mRNA MBP and glycoproteins MAG and MOG but not on myelin ultrastructure.